2021
DOI: 10.1128/msystems.00580-20
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Interactions between Brachypodium and Pseudomonas fluorescens under Controlled Iron-Limited Conditions

Abstract: Iron (Fe) availability has well-known effects on plant and microbial metabolism, but its effects on interspecies interactions are poorly understood. The purpose of this study was to investigate metabolite exchange between the grass Brachypodium distachyon strain Bd21 and the soil bacterium Pseudomonas fluorescens SBW25::gfp/lux (SBW25) during Fe limitation under axenic conditions. We compared the transcriptional profiles and root exudate metabolites of B. distachyon plants grown semihydroponically with and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…Interestingly, proteins with this domain were previously observed to be overaccumulated in response to heat stress (after 6 h and 12 h) in rice [70]. The gene encoding this protein with a Barwin domain was also found to be upregulated in B. distachyon roots inoculated with Pseudomonas fluorescens SBW25 [71]. Taken together, this suggests the importance of Bradi4g14920 in the response to heat stress as well as in root defence mechanisms in response to bacterial colonisation.…”
Section: Proteins With Interaction Domains (With Proteins or Polysaccharides)mentioning
confidence: 72%
“…Interestingly, proteins with this domain were previously observed to be overaccumulated in response to heat stress (after 6 h and 12 h) in rice [70]. The gene encoding this protein with a Barwin domain was also found to be upregulated in B. distachyon roots inoculated with Pseudomonas fluorescens SBW25 [71]. Taken together, this suggests the importance of Bradi4g14920 in the response to heat stress as well as in root defence mechanisms in response to bacterial colonisation.…”
Section: Proteins With Interaction Domains (With Proteins or Polysaccharides)mentioning
confidence: 72%
“…P. donghuensis strains also produce 7-hydroxytropolone (7-HT) – a compound with iron-scavenging and antimicrobial properties (21, 106, 107). Some microorganisms can use exogenous siderophores, therefore shifting the energetic cost of their production to other organisms (108). This phenomenon is sometimes referred to as ‘sierophore piracy’ (109).…”
Section: Discussionmentioning
confidence: 99%
“…Boiteau et al, (108) have found that the production of phytosiderophores was increased in B. distachyon following inoculation with P. fluorescens SBW25 compared to the amount in sterile roots. Moreover, in response to Fe deficiency, the P. fluorescens consumed the plant-derived siderophores present in the exudates rather than producing its own (108). It therefore seems that rhizosphere-associated pseudomonas generally do not suffer from iron starvation when supplied with root exudates.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, being able to kill these organisms would provide nutrients for the biocontrol organisms, thus augmenting the carbon-rich metabolites in the root exudates. A comparison of the root exudate composition shows that colonization of the roots by beneficial microbes alters the composition of amino acids [ 69 , 70 , 71 ]. Some amino acids presumably supply essential N for microbial growth, which is limited in the soil pore water.…”
Section: The Array Of Isolates and Their Products For Biocontrol Of M...mentioning
confidence: 99%
“…Some amino acids presumably supply essential N for microbial growth, which is limited in the soil pore water. For instance, Boiteau et al [ 70 ] found that the concentration of two N-containing amino acids in root exudates from Brachypodium decreases after colonization by Pseudomonas fluorescens . Microbes that are rhizosphere colonists have higher numbers of amino acid and sugar transporters than non-colonists [ 69 ].…”
Section: The Array Of Isolates and Their Products For Biocontrol Of M...mentioning
confidence: 99%